Primary school teachers' perceptions of differentiated instruction (DI) in Awi administrative zone, Ethiopia - Tadesse Melesse Merawi (College of education, Bahir Dar University, 2023)
Abstract Using a sequential mixed methods design, this study was conducted to investigate primary school teachers' perceptions on DI. Data were collected from randomly selected 492 primary school teachers, school principals, students and woreda education officers of Awi administrative zone, via the adapted questionnaire, semi structured interview and FGD. The reliability coefficient of the instrument was calculated using Cronbach alpha as 0.95. Data were also analyzed quantitatively using mean, standard deviation, one sample t-test, independent samples t-test and one-way ANOVA and qualitatively through thematic analysis, descriptions and narrations. The main findings of the quantitative data revealed that the majority of primary school teachers' perceptions up on the overall relevance of DI was high. In terms of variables, perception differences of teachers based on sex, qualification, in-service training and teaching experience were observed. Moreover, the qualitative data garnered also revealed varied responses up on teachers' perceptions based on the variables mentioned. Accordingly, the perceptions of the participants to address students' background knowledge, interest, readiness, learning style., learning preference and multiple intelligence through content, process, learning environment and product differentiation also varies. Thus, the study concluded that many teachers teach diversified learners in the same classroom in a form of 'one-size-fits all approach' without significantly addressing the students' readiness, interest, learning style, learning preference and multiple intelligence due to a number of reasons such as: lack of knowledge and training, overload work, scarce resources or facilities, lack of incentives for effective teachers, low commitment of teachers, weak school leadership support, lack of conducive environment for differentiation, and the like. Therefore, it is timely to re-visit the primary school teaching process and teachers' perceptions across the country and in the Amhara Region to assist all students attain at least the minimum learning competency of each grade level.